Guiding Clients Towards Self-Kindness and Acceptance: Wrestling With the Inner Critic - Mark Pearson; Helen Wilson (Psychotherapy and Counselling Journal of Australia)
Research and methodology on the treatment of self-criticism in counselling is limited in the recent literature. This article describes how harsh automatic self-criticism became viewed within several theoretical frameworks as a sub-personality with a purpose rather than a simple psychological mechanism. The article reviews a number of approaches to therapeutic work with clients experiencing habitual self-criticism. It outlines eight therapeutic steps to gaining freedom from the inner critic, including getting to know self-critical "voices", understanding their origins, recognising what activates escalation of self-criticism, and making efforts that create distance from the corrosive effect of self-criticism. Ways to become grounded and self-compassionate, and to develop an individualised wellbeing plan are discussed as components of gaining freedom from self-critical dominance.